Physical characterization of swine and human skin: Correlations between Raman spectroscopy, Tensile testing, Atomic force microscopy (AFM), Scanning electron microscopy (SEM), and Multiphoton microscopy (MPM). Issue 4 (20th November 2020) - Labroo, Pratima; Irvin, Jennifer; Johnson, Joshua; Sieverts, Michael; Miess, James; Robinson, Ian; Baetz, Nicholas; Garrett, Caroline; Sopko, Nikolai
Abstract: Background: Swine dorsum is commonly utilized as a model for studying skin wounds and assessment of dermatological and cosmetic medicaments. The human abdomen is a common location for dermatological intervention. Objective: This study provides a correlation between spectral, mechanical, and structural characterization techniques, utilized for evaluating human abdominal skin and swine dorsum. Methods: Raman spectroscopy (RS), tensile testing, ballistometry, AFM, SEM, and MPM were utilized to characterize and compare full‐thickness skin properties in swine and human model. Results: RS of both species' skin types revealed a similar assignment of vibrations in the fingerprint and the high wavenumber spectral regions. Structural imaging and mechanical characterization using ballistometry and tensile testing displayed differences in the inherent functional properties of human and swine skin. These differences correlated with variations in the Raman peak ratios, collagen intensity measured using SEM and MPM and collagen density measured using AFM. Conclusion: A comprehensive evaluation of swine skin as a suitable substitute for human skin for mechanical and structural comparisons was performed. This data should be considered for better understanding the swine skin model for cutaneous drug delivery and wound applications. Additionally, correlation between RS, tensile testing, AFM, SEM, and MPM was performed as skin characterization tools.